Food safety traceability readiness of cabbage and eggplant farmers - Melodee Marciana E. de Castro; Jewel Joana S. Cabardo (Annals of Tropical Research)
A growing global concern on food safety has much more been emphasized at the time of the pandemic. This includes the internal control system (ICS) for conventional safe farming, which has proven its ability to control pesticide residue within the safe and sustainable maximum limits for cabbage and eggplant compliant with the most stringent regulations implemented globally. Cabbage and eggplant farmers have realized the benefits of safe and sustainable production of cabbage and eggplants. To maintain safe quality food throughout the chain, a system of tracing is of utmost importance. This study proposes a traceability system to ensure that food safety is sustained throughout the value chain in the case of cabbage and eggplant and evaluates farmer readiness in food safety and traceability. In this study, farmer readiness is further described in terms of preparedness, willingness and potential to adopt. Results show that the cabbage and eggplant farmer clusters in Benguet and Quezon were not yet fully prepared in terms of actual practice but have acknowledged the importance of implementing necessary Good Agricultural Practices measures. This exhibits a positive response towards potential adoption of a food safety traceability system. Thus, to further enhance farmers’ readiness, farming consolidation in order to develop a sense of accountability and responsibility to other farmers would serve as “each other’s push” to ensure successful delivery of farmer clusters’ food safety standards.